Publication rate of abstracts presented in a Brazilian experimental surgery congress - Brito,Marcus Vinicius Henriques (2016)
ABSTRACT PURPOSE: To verify the publication rate of the abstracts presented at the XII Brazilian Congress of Experimental Surgery. METHODS: We performed a cross-sectional study that evaluated if the abstracts accepted for presentation at the XII Brazilian Congress of Experimental Surgery were published in periodics. The information was acquired using the Scielo, Medline / Pubmed, LILACS and Google Scholar databases. RESULTS: From all the abstracts presented, only 77 (40.52%) were published in scientific journals. Of this total, 14 (18.18%) were published prior to the conference 35 (45.45%) in the same year that occurred congress, 56 (72.72%) in the period 2011-2013 and 63 (81, 81%) between the Congress and the year 2015. Regarding the geographical distribution of summaries, 42 (22%) were from the northern region, 19 (10%) from the Northeast, 8 (4%) Midwest, 116 (61%) from the Southeast and 5 (3%) from the south. CONCLUSION: The publication rate of the abstracts presented at the XII Brazilian Congress of Experimental Surgery was 40,52%, most from the state of Sao Paulo.